Barriers and recommendations for colorectal cancer screening in Africa. Issue 1 (31st December 2023) - Lee, Rebecca; Holmes, David
ABSTRACT: Background: Colorectal cancer (CRC) is the third most common cancer worldwide. The incidence of CRC is rising in low- and middle-income countries but decreasing in high-income countries due to the widespread use of surveillance colonoscopy. In Africa, the implementation of screening programs remains a challenge, even in countries, such as Ghana that have established CRC screening guidelines. Objective: The purpose of this review was to identify the barriers and recommend strategies for implementing CRC screening in African countries. Methods: A literature search using PubMed was conducted with the following search terms: colorectal neoplasm, early detection of cancer, mass screening, colonoscopy, faecal occult blood test, faecal immunochemical test (FIT) and Africa. After inclusion and exclusion criteria were applied, a total of 13 articles were reviewed. Results: The most common barriers reported were limited endoscopic capacity, poor knowledge of CRC and CRC screening, health care factors, cultural factors and sociodemographic factors. Recommendations to increase the availability of CRC screening tests were to include the use of FITs, to provide more training for health care providers, and to expand educational programs for patients, physicians, and religious/community leaders. Conclusion: The primary barrier to screening for CRC in Africa is the limited endoscopic capacity, specifically the lack of infrastructure and trained personnel, which requires systematic changes by governing bodies. In addition, health care professionals should be involved in educating patients about CRC and CRC screening. Further research is needed to clarify the factors related to subtypes of CRC and to explore the feasibility of using FITs in Africa.